SIMULASI DISTRIBUSI AIR BERSIH DENGAN ADOBE FLASH - Dwi Kartikasari; Nur Nafi’iyah (Kadiri University, 2019)
The use of software in the design of clean water distribution is not new. Commonly software was used specifically was designed for clean water distribution networks, namely Epanet 2.0 and WaterCAD. So that in this research was tried using general software multimedia-based namely Adobe Flash. The stages of making simulation with the Adobe Flash program include: (1) Making a storyline, which is making a layout for planning map for clean water distribution networks. (2) Making images and symbol, including pictures of reservoir location, hamlet locations, village road, while symbol was used to determine the water flow direction from the water source to the reservoir and to each hamlet. (3) making water distribution simulation was described by arrows in the pipe, namely from the water source to the reservoir, also distributed to each village. (4) Finishing stage (finishing), which publishes work files Adobe Flash, namely .fla to file in the form of .swf and .exe. So that files can be run without installing Adobe Flash software. Keywords: Simulation; Clean Water Distribution; Adobe FlashPenggunaan perangkat lunak dalam desain distribusi air bersih bukanlah hal baru. Umumnya perangkat lunak yang digunakan khusus dirancang untuk jaringan distribusi air bersih, yaitu Epanet 2.0 dan WaterCAD. Sehingga dalam penelitian ini dicoba menggunakan perangkat lunak umum berbasis multimedia yaitu Adobe Flash. Tahapan pembuatan simulasi dengan program Adobe Flash meliputi: (1) Membuat alur cerita, yaitu membuat tata letak untuk merencanakan peta untuk jaringan distribusi air bersih. (2) Membuat gambar dan simbol, termasuk gambar lokasi reservoir, lokasi dusun, jalan desa, sedangkan simbol digunakan untuk menentukan arah aliran air dari sumber air ke waduk dan ke setiap dusun. (3) membuat simulasi distribusi air digambarkan dengan panah di pipa, yaitu dari sumber air ke waduk, juga didistribusikan ke setiap desa. (4) Finishing stage (finishing), yang menerbitkan file kerja Adobe Flash, yaitu .fla ke file dalam bentuk .swf dan .exe. Sehingga file dapat dijalankan tanpa menginstal perangkat lunak Adobe Flash. Kata Kunci: Simulasi; Distribusi Air Bersih; Adobe Flash